2022
DOI: 10.3389/fnut.2022.866400
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Dietary Patterns and Chronic Diseases in Rural Population: Management Plays an Important Role in the Link

Abstract: ObjectiveHealth dietary pattern is related with reduced risk of chronic metabolic disease, but the benefits were not fully clear in the Chinese population. The aim of this study was to explore the association between dietary patterns and multiple chronic metabolic diseases in middle-aged and elderly Chinese.MethodsA total of 718 Chinese adults aged ≥ 45 who lived in the Huairou regions of Beijing were included in the present cross-sectional analysis from 2019 to 2020. Dietary data were obtained by food frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A relationship between dietary patterns and chronic diseases has been shown in the literature. 22 However, it is also known that adults who have multiple chronic disease risk factors reported poorer diet quality. 23 Taylor et al 24 have reported that nutrition literacy may predict adherence to a healthy or an unhealthy diet pattern in adults who have a nutrition-related chronic condition.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between dietary patterns and chronic diseases has been shown in the literature. 22 However, it is also known that adults who have multiple chronic disease risk factors reported poorer diet quality. 23 Taylor et al 24 have reported that nutrition literacy may predict adherence to a healthy or an unhealthy diet pattern in adults who have a nutrition-related chronic condition.…”
Section: Discussionmentioning
confidence: 99%
“…The literature highlighted that in rural areas of developing countries, the elderly population heavily relies on government or charitable organizations for financial support in managing chronic diseases [24]. However, the number of chronically ill elderly is rising, and the existing assistance methods are insufficient to adequately address the expenses associated with chronic diseases [25]. In response to the challenge of limited income for managing chronic conditions in rural Chinese areas, this paper presents a Sustainable Health Product-Service System Design Model.…”
Section: Model Constructionmentioning
confidence: 99%
“…6 Additionally, research in China suggests that excessive energy intake contributes to the high incidence of stroke and hypertension, with high consumption of edible salt being the major cause of these conditions in northern China. 7,8 Given that most NCDs are chronic and reversible, an efficient way to control NCDs is educating individuals on healthy lifestyles, such as eating well-balanced diet and exercising regularly. 9,10 The World Health Organization (WHO) currently recommends that adults carry out at least 150 minutes of moderateintensity aerobic exercise or 75 minutes of vigorous aerobic exercise each week.…”
Section: Introductionmentioning
confidence: 99%